Effect of four tillage methods and two forms of urea placement on physical properties of an Ultisol of savanna sowed with three sesame varieties - Méndez Natera, J.; Medina Leota, O.; Merazo Pinto, J.; Fendel Alvarez, J. (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2012)
The main objective of this study was to determine the effect of four tillage systems and placement of urea on water content (WC), bulk density (BD), vacuum relationship (VR) and porosity (P) of an Ultisol of savanna sowed with three sesame varieties (Sesamum indicum L.). The experiment was carried out at the Estación Experimental de Sabana de la Universidad de Oriente. The statistical design was a split-plot with special arrangement of the treatments assigned to the main plots, being these, four tillage methods (TM): a) Chisel (C): a pass of chisel plow 30 days before sowing (DBS) and a pass of rotary cultivator 1 DBS, b) Harrow (H): three passes of H at 30, 15, and 1 DBS (conventional method), c) minimum tillage (MT): a pass of rotary cultivator 1 DBS and, d) Chisel +Harrow: a pass of C 30 DBS and three passes of H at 30,15, and 1 DBS. The subplots were constituted by a factorial arrangement of three varieties (V) viz., ’Glauca’, ’Acarigua’ and ’Blanca’ and two forms of urea placement (FUP), 200 kg/ha 30 days after sowing (DAS): banded into the soil and banded on soil surface, for a total of 24 treatments with three replications. Arate of 500 kg/ha of 12-24-12 was applied at the moment of sowing. The weed control was carried out applying Dual, Linurex and Gramoxone at 2, 0.5, and 3 L/ha respectively 1 DAS, in all the treatments. The soil samples were taken 52 and 99 DAS. The results showed that at the 52 DAS the soil with highest WC was in the plots sowed with ’Blanca’. BD, VR and P were similar in all the TM in the three cultivars. The plots sowed with ’Blanca’ presented the lowest BD, the biggest VR and P with the ML, the plots sowed with ’Glauca’ and ’Acarigua’ presented the lowest BD, a bigger VR and P with C and H, while in the method C+H, the plots presented similar BD, VR and P in the three cultivars. At the 99 DAS, for the FUP, the lower BD and larger P were in the plots where urea was placed banded on soil surface. In relation to the TM, the lower BD, the larger VR and P were in the treatments C, C+HandML.